2016
DOI: 10.1002/em.22067
|View full text |Cite
|
Sign up to set email alerts
|

High pesticide exposure events and DNA methylation among pesticide applicators in the agricultural health study

Abstract: Background Pesticide exposure has been associated with acute and chronic adverse health effects. DNA methylation (DNAm) may mediate these effects. We evaluated the association between experiencing unusually high pesticide exposure events (HPEEs) and DNAm among pesticide applicators in the Agricultural Health Study (AHS), a prospective study of applicators from Iowa and North Carolina. Methods DNA was extracted from whole blood from male AHS pesticide applicators (n=695). Questionnaire data were used to ascer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 76 publications
(112 reference statements)
1
26
0
8
Order By: Relevance
“…We observed a global hypomethylation and promoter-specific hypermethylation in male germ cells. It is not surprising to observe global DNA hypomethylation and hypermethylation in specific genes, this is a phenomenon commonly described in cancer development (Fotouhi et al, 2014), including prostate cancer (Cho et al, 2006), and it was recently reported in pesticide applicators exposed to a mixture of pesticides (Rusiecki et al, 2017). Currently, there is no clear mechanism that could explain the occurrence of both hypomethylation and hypermethylation events at the same time, but these phenomena could be caused by independent mechanisms (Roman-Gomez et al, 2006) that require being further investigated.…”
Section: Discussionmentioning
confidence: 91%
“…We observed a global hypomethylation and promoter-specific hypermethylation in male germ cells. It is not surprising to observe global DNA hypomethylation and hypermethylation in specific genes, this is a phenomenon commonly described in cancer development (Fotouhi et al, 2014), including prostate cancer (Cho et al, 2006), and it was recently reported in pesticide applicators exposed to a mixture of pesticides (Rusiecki et al, 2017). Currently, there is no clear mechanism that could explain the occurrence of both hypomethylation and hypermethylation events at the same time, but these phenomena could be caused by independent mechanisms (Roman-Gomez et al, 2006) that require being further investigated.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies investigating epigenetic alterations in PD have used experimental cell culture models of PD; however, there have been very few human studies that have investigated this link. Moreover, the impact of altered inflammatory gene promoter DNA methylation on disease development in agricultural workers exposed to high levels of pesticides (Rusiecki, et al, 2017) will provide an opportunity to evaluate the influence of pesticide exposure on the alteration of epigenetic patterns associated with PDrelated inflammatory genes. In particular, determining the association between high pesticide exposure events and the DNA methylation of inflammatory genes in the blood of male pesticide applicators may provide insights into the relationship between gene inactivation and the development of neurobehavioral deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides are complex mixtures and present genotoxic agents, and several studies have strongly associated occupational exposure with DNA damage [ 10 , 14 16 , 18 , 19 ], oxidative stress generation [ 10 , 14 , 42 ], impairments to reproductive [ 42 ] and immune systems [ 43 ], and epigenetic alterations (reviewed by [ 25 ]), among others. Recently, a consortium called Agricultural Health Study (AHS) has approached the influence of exposure to pesticides in crop farms to telomere length, although those studies are not clear which pesticides, whether as pure or mixture use, and which crop are being investigated [ 44 , 45 ]. Our group demonstrated shorter telomere length in tobacco farmers, exposed to both pesticides and nicotine from tobacco leaves, is associated with increased oxidative stress levels and trace and ultratrace element status [ 17 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group demonstrated shorter telomere length in tobacco farmers, exposed to both pesticides and nicotine from tobacco leaves, is associated with increased oxidative stress levels and trace and ultratrace element status [ 17 , 46 ]. Along with the available data in literature, the influence of pesticides on telomere length demonstrates that occupational exposure to pesticides presents a long-term effect on farmers [ 7 , 11 , 13 , 21 , 30 , 31 , 42 , 44 , 47 ]. The wild type of PON1 Gln192Arg , a polymorphism directly involved in metabolizing organophosphate pesticides, was found to be associated with an increase in buccal micronucleus in tobacco farmers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%